Lembaga Ngaji Duduk Pulau Bangka Tahun 1864-2022 Gerakan Keagamaan Dan Semangat Pendidikan Islam - Subri; Rudini (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This research focuses on analysing religious movements and the spirit of Islamic education from the Bangka Island study by a sitting institution—data collection methods through observation, interviews and documentation with qualitative analysis of historical approaches. The research findings show that the study by a sitting institution is a historical fact of a traditional institution with distinctive characteristics such as the uniqueness of the curriculum, learning methods, and learning models. The spirit of Islamic education in the intensification of Islam increases the interaction of students with teachers, the level of religious adherence and the strengthening of the aspects of tauhid, akhlak, and fiqh. Then the religious movement; directed society, acculturation occurs in society on adab, communication interactions, and inspires the growth of arab schools and several madrasah diniyah.